Effect of Force Level and Gender on Pinch Force Perception in Healthy Adults. (May 2020) - Li, Lin; Li, Yanxia; Wang, Huihui; Chen, Wenqi; Liu, Xinyu
This study investigated the effects of both force level and gender on pinch force reproduction errors in normal participants during an ipsilateral force reproduction task. In total, 20 healthy participants were asked to generate a range of levels of reference forces ranging from 5% to 60% maximal voluntary isometric contraction (MVIC) in increments of 5% MVIC using the tip pinch and to reproduce these forces using the same hand. The results showed that the males more accurately and consistently reproduced the forces than did the females, and the most accurate estimation occurred at approximately 20% to 35% MVIC. This finding can help us better understand the reasons for the higher rate of musculoskeletal disorders in females than in males and to develop tools and preventive strategies to decrease the rate of hand injuries in both genders.